FEATURES OF SOCIAL PERCEPTION IN CHILDREN OF PRESCHOOL AGE - Huzeeva , G.R. (Modern Psychology, 2019)
The article discusses the development of the emotional and cognitive component of the social adult’s image, the peer image and the perception features of the problematic situations of communication in the interaction space with peers in children 5-7 years old. From the article it is shown that the development of the emotional component is ahead of the development of the cognitive component of the social image. At the same time, the content and structure of the image of a social adult person and the image of a peer have both similarities and differences. Features of the image of an adult, peer and features of perception and problem solving reflect the basic patterns of children’s communication development. The relationship was found between the level of popularity in the peer group and the level of social perception in older children. The influence of social context on the development of social perception in children 5-7 years old is shown. The article identifies the problem of developing technologies that accompany the social development of preschoolers.